Pengaruh Technology Acceptance Factor, Website Service Quality Terhadap Customer E-Loyalty Yang Di Mediasi Oleh Customer E-Satisfaction (Studi Empiris Pada Konsumen Pengguna Tokopedia Di Kota Padang) - Nanang Rinaldo; Abror Abror (Jurnal Kajian Manajemen dan Wirausaha, 2019)
AbstractThe purposes of this study are to analyze: (1) The effect of Technology Acceptance Factor on EcustomerSatisfaction, (2) The effect of Website service quality on E-customer Satisfaction, (3)The effect of E-customer Satisfaction on E-customer loyalty, (4 ) The Effect of TechnologyAcceptance Factor on E-customer loyalty, (5)The effect of Website service quality on E-customerLoyalty. The population on this study is Tokopedia customers in the city of Padang. We used200 customers as the respondent. This study used survey method with questionnaires as the data.This study analyzed the data by using SEM with smart PLS 3.0 as the software. The results ofthis study indicate that: (1) Technology Acceptance Factor has no significant effect on customerloyalty. (2) Website service quality has a significant effect on E-customer loyalty. (3) E-customersatisfaction does not affect the E-customer loyalty significantly. (4) Technology AcceptanceFactor affect E-customer satisfaction significantly. (5) Website service quality has a significantinfluence on E-customer satisfaction.Keywords: Customer e-loyalty, Customer e-satisfaction, Technology acceptance factor & Webservice quality.